Pressure management in pipe distribution system at Kuantan district - Safuan Fathy, Amran (2013)
In pipe distribution system, there is a lot problem occur if pressure not handling in proper way, this is because it will affect water delivery rate, demand rate, pressure rate and other side problems. Based On (O'Day, 1987), there are low pressure and high head loss problems in pipe. The effective of the pipe distribution design are in question because this factor will abruptly change effectiveness of pressure, automatically will let the change in pressure management task. The purpose of this study is to determine the effectiveness of pressure management taken by PAIP after executed a pressure setting by follow KPI value at Kuantan and methods taken to solve pressure problem at Paya Bungor. The data were obtained from 53 pressure gauge of Kuantan district piping distribution system. The findings of the study divided into two parts based on the objective which is uncover method of pressure management that solved low pressure and demand rate. Besides that, for the past two months of this implementation range pressure, the percentage of two months data was calculated and also the percentage of effectiveness after one year. The contributing factors for effectiveness to increase are pressure management that PAIP taken. Therefore, the result will analyses what are the method and numbers to solved pressure problems. The significant of this study is to get maximum pressure effectiveness toward better pressure rate and less problem encounter in the future.